Effectiveness of multigene analysis for associating dimorphic partners in flat wasps (Hymenoptera, Bethylidae, Dissomphalus) - Fagundes, Valéria; Monjardim, Marina; Martinelli, Arturo B.; Mugrabi, Daniele F.; Azevedo, Celso O. (Zootaxa, 2024)
DNA sequences have proved valuable for associating males and females of the same dimorphic species in Hymenoptera. These molecular associations, however, depend on the used DNA sequences and the analysis methods. In the present study, we evaluated the molecular associations on 23 species of Dissomphalus (Hymenoptera, Bethylidae) using the three most common DNA sequences in molecular studies of Hymenoptera (28S rRNA, COI and ITS2). Our results indicated the male-female association with these three markers. COI, however, showed to be more suitable than the other markers because there was no overlap of genetic variation among species. In contrast, the 28S rRNA showed overlapping of genetic distance limits, indicating that the distance matrix is not enough to assign a sexual conspecificity. We were able to perform female association to the described species D. verus Mugrabi & Azevedo, demonstrating that phylogenetic analysis is a valuable tool for associating the sexes of dimorphic species.